Protease inhibitor therapy for hepatitis C virus-infection. (13th April 2018) - de Leuw, P.; Stephan, C.
ABSTRACT: Introduction : The hepatitis C virus (HCV) has affected an estimated of 80 million individuals worldwide and is a strain on public health. Around 25–30% of patients in Europe and the US who are infected with HIV are coinfected with HCV. Prior to 2013, treatment modalities containing an NS3/4A protease inhibitor in combination with pegylated interferon and ribavirin improved sustained virological response (SVR) rates. However, rates of severe side effects were high. Nowadays, oral direct-acting antiviral (DAA) combination therapy offers excellent treatment efficacy, safety and tolerability. Areas covered : This review focuses on the current literature and clinical evidence and their impact regarding NS3/4A protease inhibitors. The pitfalls encountered in treating HIV- and HBV-coinfected patients are also discussed. Expert opinion : In the era of DAA treatment, third-generation pan-genotypic NS3/4A protease inhibitors (mainly glecaprevir and voxilaprevir) show high antiviral activity and a genetic resistance barrier with cure rates of over 95% when combined with an NS5A inhibitor, irrespective of baseline resistance associated variants (RASs) being present. These new key components of DAA combination therapy are impressive options to eradicate HCV in the so-called difficult-to-treat population (e.g. compensated cirrhosis, end-stage renal disease and patients who failed previous DAA treatment).